Effects of maternal fructose intake on the offspring’s kidneys - Argeri, Rogério; Nishi, Erika Emy; Kimura Lichtenecker, Débora Conte; Gomes, Guiomar Nascimento (Frontiers in Physiology, 2022)
Fructose overload has been associated with cardiovascular and metabolic disorders. During pregnancy, these alterations may affect the maternal environment, predisposing the offspring to diseases. Aims: To evaluate renal morphology and function of the offspring of dams that received fructose overload during pregnancy and lactation. Methods: Female Wistar rats were distributed into Control (C) and Fructose (F) groups. C received food and water ad libitum; F received food and D-fructose solution (20%) to drink ad libitum. D-fructose offer started one week before mating and continued during pregnancy and lactation. The progeny were designated as Control (C) or Fructose (F); after weaning half of F received water to drink (FW) and half received D-fructose (FF). At four months of age, blood pressure (BP) and renal function were evaluated. The expressions of sodium transporters (NHE3-exchanger, NKCC and NCC-cotransporters, and ENaC channels); markers of renal dysfunction: ED1 (macrophage), eNOS, 8OHdG (oxidative stress), renin and ACE 1 and 2 were evaluated. CEUA-UNIFESP: 2757270117. The group FF presented: reduced glomerular filtration rate, and urinary osmolarity; increased BP, proteinuria, glomerular hypertrophy, macrophage infiltration, increased expressions of transporters (NHE3, NCC, and ENaC), 8OHdG, renin and ACE1. The FW did not show increased BP and renal functional alterations; however, it presented glomerular hypertrophy, macrophage infiltration, and increased expression of the transporters (NHE3, NKCC, NCC, ENaC), renin, and ACE1. These data suggest that fructose overload during fetal development altered renal development resulting in increased expression of renin, ACE1, and sodium transporters, thus, predisposing to hypertension and renal dysfunction.